Genetic diversity and variability in two Italian autochthonous donkey genetic types assessed by microsatellite markers - Donato Matassino (Italian Journal of Animal Science, 2014)
Since 13rd century, Italian domestic autochthonous donkey population has been characterised by Mediterranean grey mousy cruciate ancestral phenotype, currently typical of Amiata donkey (AD) genetic type. This phenotype persisted up to the 16th century when a marked introduction of Hispanic and French big sized and dark bay or darkish coloured sires occurred. In the context of a safeguard programme of Latial Equide resources, the aim of this research was to evaluate the genetic diversity and similarity between the AD breed and an autochthonous donkey population native from Lazio, the Viterbese donkey (VD), using molecular markers. A total of 135 animals (50 AD and 85 VD) were genetically characterised by using 16 short tandem repeat markers. A high genetic differentiation between populations (FST=0.158; P<0.01) and a low betweenbreeds genetic similarity (0.233±0.085) were observed. Correspondence analysis, the result of STRUCTURE software analysis and analysis of molecular variance would seem to indicate genetically different entities as well. It would be desirable to increase the number of comparison with other breeds to better understand the origin of VD. Moreover, results obtained in this study suggest that the loss of genetic variation observed in VD could mainly derive from unnoticed sub-population structuring (Wahlund effect), rather than to other factors such as inbreeding, null alleles or selection influence.